Islam and Early Modern English Literature - Robinson, Benedict S. author. aut Link
XI, 237 p.
Keywords: This book traces the process through which authors like Spenser, Shakespeare, and Milton adapted, rewrote, or resisted romance, mapping a world in which new cross-cultural contacts and religious conflicts demanded a rethinking of some of the most fundamental terms of early modern identity.